2022
DOI: 10.1186/s12544-022-00555-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing disruptive mobility scenarios for rural areas. Participatory mobility scenario building in a Belgian village for the year 2050

Abstract: Background Historically, quantitative forecasting methods have been used in transport planning. As forecasts can be unreliable to plan for the medium- and long-term, scenario building has recently been increasingly used. However, scenario building methods often fail to take disruptions and wild cards into account, i.e., low probability but high impact events. When unaccounted for, wild card events, like the COVID-19 pandemic, lower the efficacy of scenario building in policy making, as these ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…These results in that the power supply cannot be connected during the use of the terminal device, and only external batteries can be used for power supply, which makes the application of the terminal have power consumption problems. If the device consumes a lot of power, the battery needs to be replaced frequently, which seriously affects the effective performance of the IoT function and increases the workload of the relevant personnel [4].…”
Section: Introductionmentioning
confidence: 99%
“…These results in that the power supply cannot be connected during the use of the terminal device, and only external batteries can be used for power supply, which makes the application of the terminal have power consumption problems. If the device consumes a lot of power, the battery needs to be replaced frequently, which seriously affects the effective performance of the IoT function and increases the workload of the relevant personnel [4].…”
Section: Introductionmentioning
confidence: 99%
“…[20], who found that the use of e‐bikes and personal mobility vehicles, such as e‐scooters, is not significant, probably also due to higher average age of the population, a characteristics in common to both UK and Spain. However, in the context of potential future for rural mobility, bicycles and scooters are favoured for short trips over cars in Belgium [17], when multigeneration approach is carried out. Tori et al.…”
Section: Discussionmentioning
confidence: 99%
“…DRT remains the most popular service to flex and adapt to a dispersed demand [27]; however, other mobility services might be more appropriate if the focus is shifting to a multimodal mobility rather than increasing the need for infrastructure investment. Tori et al [17] used co-creation techniques and participatory methods to interview a sample of 14 residents from a small village in Belgium for developing a vision for rural mobility. Investigating on future of mobility scenarios is a common method widely used for transitioning towards sustainable mobility in cities for Sustainable Urban Mobility Plans (SUMPs).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations